Influence of Individual Values Dissimilarity in the Outcome of top Management Teams: a study in a management lab - D'Acosta Rivera, Jorge Ramon; Domenico, Silvia Marcia Russi de; Sauaia, Antonio Carlos Aidar (Review of Business Management, 2014)
Several studies relate organizational outcomes to the performance of top management teams (TMT). Some of these studies suggest that the process of strategic choice is influenced by the cognitive background and values of the executives in those teams, and have focused on the composition of TMT, using demographic variables as proxies for deep-level characteristics. The aim of this descriptive and exploratory study was to verify directly the influence of deep-level characteristics – the dissimilarities of TMT members’ individual values – on the team outcomes. This research was carried out using a quantitative method within a public university management lab environment located in the city of São Paulo, applying two value surveys validated in Brazil on TMT composed of Business Management and Accounting undergraduates submitted to a business game situation, resulting in a non-probabilistic sample formed of 32 teams comprising 186 students with valid responses. Through multiple linear regression technique, two statistically significant regression models were found. It was found that the improved performance of TMT occurs when members differ in the importance assigned to values related to openness to change and have similar appreciation of values related to rules and to security in life (conservation values ) and the pursuit of power (prestige), giving evidence that this can occur not only in a laboratory environment, but also in the business environment, where time pressures and competition are even more severe and, therefore, more subject to deep-level subjective characteristics. Keywords: Personal values. Work values. Top management teams. Team outcomes. Management lab.